(untitled) (Commonwealth Journal of Local Governance, 2010)
The theme of this year’s Commonwealth Local Government Conference was Improving local government: the Commonwealth vision. This theme is fundamental to all of us working in and with local government, but particularly so in the current economic climate where councils are having to once again look at how they can tighten their purse strings while they are facing greater demands with less income - doing more with fewer resources. The conference was held in Freeport, Grand Bahama, hosted by the Government of the Bahamas and the councils of Grand Bahama at the Our Lucaya Conference Centre. More than 550 local government ministry, association and council representatives from 48 countries attended the conference. Previous conferences set out Aberdeen Agenda and Auckland Accord as to the kind of local government we want to strive to achieve: local democracy and good governance for effective services to respond to the needs of the local community and strong local leadership to drive development and support local communities. This conference builds on these previous outcomes, with speakers and delegates calling for local government to continue to improve as part of a broader process of development. Jamaican Minister Robert Montague summed up what is needed as a shift in attitude to include the public as important partners – a shift he called ‘business unusual’ to encompass improving service delivery, improving revenue streams, increasing community dialogue, finding new partners and leading from the front.